What does the 4th edition of the World Health Organization Classification of Head and Neck Tumors (2017) bring new about mucosal melanomas? - José Cândido Caldeira Xavier Júnior; Juliana Polizel Ocanha-Xavier (Sociedade Brasileira de Dermatologia, 2018)
Abstract: The recently published 4th Edition of the World Health Organization Classification of Head and Neck Tumors addresses the most relevant and updated aspects of tumor biology, including clinical presentation, histopathology, immunohistochemistry, and prognosis of head and neck tumors. The objective of the present study is to compare these updates to the 3rd edition of that book with regard to mucosal melanomas and to highlight the potential factors that differ those tumors from cutaneous melanomas. We observed progress in the understanding of oral and sinonasal mucosal melanomas, which also present themselves, in the molecular scope, differently form cutaneous melanomas.